(untitled) (Baghdad Science Journal, 2016)
This study aimed to determine the effect of varicocelectomy on sperm parameters, oxidant- antioxidant status and chromatin maturity percent. The current study has been conducted on 154 infertile patients complaining from varicocele and varicocelomized men in addition to 25 fertile men as control. The results revealed significant decrease (P